An innovative model for WEEE recovery network management in accordance with the EU directives. (14th March 2008) - Gamberini, Rita; Gebennini, Elisa; Grassi, Andrea; Mora, Cristina; Rimini, Bianca
An increased interest towards environmental respect amongst consumers, managers and researchers is registered, owing both to changing sensitivity and guidelines described in technical regulations. In this scenario, the European Union (EU) directives 2002/96/EC and 2003/108/EC, controlling the management of Wastes of Electric and Electronic Equipments (WEEE) are well-inserted. Companies producing Electric and Electronic Equipments (EEE) become responsible for end of life steps of their products. Hence, great efforts are made to optimise both recovery networks and remanufacturing and recycling processes. This paper proposes an innovative model for recovery network management. Included is a case study.